Asi Tidak Eksklusif Dan Imunisasi Tidak Lengkap Sebagai Faktor Risiko Kejadian Stunting Pada Balita - Afrinda Graharani Sandra; Muhammad Shoim Dasuki; Tri Agustina; Nining Lestari (INVOLUSI: Jurnal Ilmu Kebidanan, 2021)
Toddlers are the next generation of a nation so they need special attention. 155 million children under five in the world are stunted. In Indonesia, there are 3.9% short toddlers, 11.5% very short toddlers, 30.7% toddlers with non-exclusive breastfeeding, and 57.9% toddlers with incomplete immunizations. This study was to determine the relationship between exclusive breastfeeding and completeness of immunization with the incidence of stunting in toddlers. This study uses an observational research type with a case control design. Using secondary data by purposive sampling with a total sample of 140, consisting of 70 cases and 70 controls at the Karanganyar Public Health Center. Data were obtained from the toddler cohort and e-PPGBM (Community Based Nutrition Recording and Reporting Application). Data were analyzed using Chi Square test for breast milk variable p value <0.001 and immunization p value = 0.021. In the logistic regression test, non-exclusive breastfeeding was at risk of stunting with OR = 8.737 and p value <0.001. Incomplete immunization is at risk of stunting with OR = 7.320 and p value < 0.001.